2015
DOI: 10.1182/blood.v126.23.2704.2704
|View full text |Cite
|
Sign up to set email alerts
|

CC-122 Expands Activated and Memory CD4 and CD8 T Cells In Vivo and Induces T Cell Activation Ex Vivo in Subjects with Relapsed or Refractory Diffuse Large B Cell Lymphoma and Multiple Myeloma

Abstract: Background: CC-122 is a first in class PPMTM pleiotropic pathway modifier compound with multiple biological activities including potent anti-proliferative activity against B lineage cells, anti-angiogenic activity and immunomodulatory effects. CC-122 binds cereblon, and promotes ubiquitination of lymphoid transcription factors Ikaros and Aiolos, leading to their subsequent degradation resulting in activation of T cells. The immunological properties of CC-122 including effects on T cell subset number in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Avadomide also induces apoptosis in multiple myeloma cells and shows antitumor activity in mouse xenograft models of DLBCL and multiple myeloma (6,8,9). In T cells, Aiolos degradation by avadomide leads to derepression of genes, including IL2, resulting in enhanced IL2 production, costimulation of T cells, and IL2-induced T-cell proliferation (1, 5,10). In addition, avadomide has been shown to activate natural killer (NK) cells and exhibits potent antiangiogenic properties, as demonstrated in an ex vivo umbilical artery sprout outgrowth assay (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avadomide also induces apoptosis in multiple myeloma cells and shows antitumor activity in mouse xenograft models of DLBCL and multiple myeloma (6,8,9). In T cells, Aiolos degradation by avadomide leads to derepression of genes, including IL2, resulting in enhanced IL2 production, costimulation of T cells, and IL2-induced T-cell proliferation (1, 5,10). In addition, avadomide has been shown to activate natural killer (NK) cells and exhibits potent antiangiogenic properties, as demonstrated in an ex vivo umbilical artery sprout outgrowth assay (9).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment options for patients with advanced solid and hematologic malignancies relapsed or refractory to standard therapies are limited. Avadomide's cell-autonomous effects, immune modulation, and antiangiogenic activity make it a potential therapeutic agent for hematologic and solid tumors (1,2,10,11). Herein, we report results from the first-in-human phase I dose-escalation study of avadomide in patients with advanced solid tumors, non-Hodgkin lymphoma (NHL), and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Avadomide also decreased CD19 + B cells and expanded cytotoxic memory T cells in patients with NHL 12,13 . Furthermore, paired biopsies from DLBCL patients showed increased infiltration of T cells and macrophages upon treatment with avadomide 11 . Avadomide has also been shown to activate NK cells that mediate antibody‐dependent, cell‐mediated cytotoxicity 14 .…”
Section: Introductionmentioning
confidence: 98%
“…In conjunction with antilymphoma activity, avadomide has immunomodulatory effects. Ex vivo studies showed that avadomide significantly activated T cells, as measured by a dramatic increase in IL‐2 secretion upon stimulation 6,11 . Avadomide also decreased CD19 + B cells and expanded cytotoxic memory T cells in patients with NHL 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation